Decentralised social media - Roel Roscam Abbing; Cade Diehm; Shahed Warreth (Internet Policy Review)
Social media platforms allow users to create digital identities, interact with other users, post and discover content. On mainstream social media platforms, aspects of the platform are centralised under the control of one umbrella. Decentralised social media are designed around the distribution of one or more aspects required to make social media function. Architecturally, these are data storage, content distribution, discovery, identity mechanisms and networking topology. Socially, these are their governance and revenue models. This article identifies and discusses three general types of decentralised social media grouped by architecture: federated, peer-to-peer, blockchain-based. Examples of each are discussed, along with a general description of their functioning and governance. Finally, the entry provides a general discussion of the drivers and issues around decentralised social media.